ORGANIZATIONAL AND ECONOMIC MECHANISM OF SUPPORT AND DEVELOPMENT OF THE FINANCIAL INDUSTRIAL GROUPS IN THE MINERAL AND RAW MATERIALS SECTOR OF KAZAKHSTAN - Galiyeva A.Kh,; Toksanova A.N,; Ukubassova G.S,; Kulubekov M.T,; Kozhabaeva S.A, (Academic Journal of Physical and Chemical Sciences, 2019)
The purpose of the article is to develop an organizational and economic mechanism for the development of corporate structures in the mineral resource sector of Kazakhstan economy in the context of deepening market transformations. To achieve the goal, methods of a systematic approach, scientific abstraction, analysis and synthesis, as well as methods of multi-criteria economic-mathematical modeling, multi-criteria optimization, expert assessments, groupings were used. The study made it possible to develop a conceptual model of organizational and economic mechanisms for the formation and development of financial and industrial groups with the definition of four main blocks of mechanisms that are interconnected by elements and components. In addition, the work has systematized measures to support the formation and development of financial-industrial groups focused on import-substituting and export-oriented production in three areas: direct impact, indirect and indirect support. The results of the study can be applied in the development of government measures to stimulate the development of financial and industrial groups not only in the mineral resource sector, but also in other sectors of Kazakhstan economy.